Heat shock protein 27 downstream of P38-PI3K/Akt signaling antagonizes melatonin-induced apoptosis of SGC-7901 gastric cancer cells. Issue 1 (December 2016) - Deng, Wenjie; Zhang, Yujie; Gu, Luo; Cui, Jie; Duan, Biao; Wang, Yueyuan; Du, Jun
Abstract Background Despite the fact that melatonin treatment shows some promise in gastric cancer, the molecular mechanisms of gastric cancer cells in response to melatonin remains to be determined. Methods The SGC-7901 gastric cancer cells were treated with different concentrations of melatonin for 24 and 48 h. Cell viability was determined by MTT assay, Hoechst 33258 staining and FACS analysis were used to detect apoptotic cells. The contents and activation of apoptosis-related proteins HSP27, Akt and P38 were evaluated by immunoblotting analysis. Then we treated SGC-7901 cells with HSP27-specific siRNA, PI3K inhibitor LY294002 or P38 inhibitor SB203580 to investigate the role of HSP27, Akt and P38 in the anti-apoptotic response of SGC-7901 cells to melatonin. Results Melatonin suppressed cell viability and stimulated apoptosis of gastric cancer SGC-7901 cells dose-dependently. Mechanistically, the observed apoptosis was accompanied by the melatonin-induced phosphorylation of HSP27. HSP27-specific siRNA transfection effectively reduced HSP27 phosphorylation and augmented melatonin-induced apoptosis, indicating that HSP27 is resistant to melatonin-induced apoptosis. Moreover, melatonin increased PI3K/Akt activation, LY294002 abrogated HSP27 activation and promoted cell apoptosis induced by melatonin. Furthermore, melatonin increased P38 activity, and P38 inhibitor SB203580 inhibited melatonin-induced PI3K/Akt, HSP27 activation and accelerated cell apoptosis. Conclusion In contrast to the well-established anti-cancer properties of melatonin, our study revealed clearly a distinguishable anti-apoptotic pathway induced by melatonin, that is, HSP27 plays a crucial role in apoptotic resistance in melatonin-treated gastric cancer cells, and its activation is most likely via the activation of P38/PI3K/Akt signaling.